2022
DOI: 10.3389/fpls.2022.853220
|View full text |Cite
|
Sign up to set email alerts
|

The Reciprocal Effect of Elevated CO2 and Drought on Wheat-Aphid Interaction System

Abstract: Due to the rising concentration of atmospheric CO2, climate change is predicted to intensify episodes of drought. However, our understanding of how combined environmental conditions, such as elevated CO2 and drought together, will influence crop-insect interactions is limited. In the present study, the direct effects of combined elevated CO2 and drought stress on wheat (Triticum aestivum) nutritional quality and insect resistance, and the indirect effects on the grain aphid (Sitobion miscanthi) performance wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…The water regime has been found to have little effect on sucrose concentration in leaf phloem exudates (Stallmann et al, 2022). Drought was found to increase total sucrose (as well as glucose and fructose) collected from leaf exudates, expressed in mg g −1 FW (Xie et al, 2022) while exudated sucrose was found to decrease (glucose and fructose being unchanged) in another study (Xu et al, 2018). In other herbaceous species such as Arabidopsis, it is generally believed that water deficit causes an increase in sucrose concentration in phloem sap [for a review, see (Lemoine et al, 2013)].…”
Section: Effects Of Water Availabilitymentioning
confidence: 97%
“…The water regime has been found to have little effect on sucrose concentration in leaf phloem exudates (Stallmann et al, 2022). Drought was found to increase total sucrose (as well as glucose and fructose) collected from leaf exudates, expressed in mg g −1 FW (Xie et al, 2022) while exudated sucrose was found to decrease (glucose and fructose being unchanged) in another study (Xu et al, 2018). In other herbaceous species such as Arabidopsis, it is generally believed that water deficit causes an increase in sucrose concentration in phloem sap [for a review, see (Lemoine et al, 2013)].…”
Section: Effects Of Water Availabilitymentioning
confidence: 97%
“…Evidence for the occurrence of hexoses has been provided with reliable phloem sap sampling techniques, including stylectomy [ 53 , 56 , 60 , 61 ], the EDTA method [ 45 , 61 , 62 , 63 , 64 , 65 ], the incision method [ 66 , 67 ] and centrifugation [ 68 ]. Fructose and glucose content depends on species (e.g., found in lemon tree, wheat and maize [ 45 , 62 ] but absent in castor bean [ 21 , 55 ]) and developmental stage; for instance, it depends on grain filling stage, N fertilization and CO 2 concentration in wheat [ 65 , 69 , 70 ]. When hexose concentration is high, it likely reflects the action of sucrose-cleaving enzymes during sampling (invertase, sucrose synthase) and/or the contribution of hexose from petiole tissues to the extract obtained by exudation [ 17 , 71 ].…”
Section: Phloem Sap Metabolitesmentioning
confidence: 99%